Explaining the Swedish 'housewife era' of 1930–1970: joint utility maximisation or renewed patriarchy?. Issue 2 (4th May 2017) - Edvinsson, Rodney; Edvinsson, Therese Nordlund
ABSTRACT: This study shows that the Swedish 'housewife era' roughly occurred in 1930–1970. During the 1950s, the ratio of women's worked hours to men's worked hours reached a low point. In the early 1970s, it rose to above 50%. We argue that models of joint utility maximisation, assuming equal gender power relations unrestrained by cultural and institutional settings, cannot alone explain this era. The two principal structural mechanisms behind the rise of the breadwinner household were the decline of the farm household and the increased proportion of married women. Both weakened the bargaining position of women. Three results in our study weaken the claims of the joint utility maximisation model. Firstly, marriage was much more important than motherhood in determining the probability of women's labour force participation, although the age of the child is then not taken into account. Secondly, the labour force participation of married women was similar across different social strata outside of the farm and top income households, indicating a prevalent capitalist patriarchal structure. Thirdly, women's leisure was valued less than men's, demonstrating that the preferences of the husband were prioritised over those of the wife.